2018
DOI: 10.1159/000488242
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates the NLRP3 Inflammasome to Induce Podocyte Injury and Mitochondrial Dysfunction

Abstract: Background: We previously reported that the NLRP3 inflammasome played an important role in mediating the podocyte injury induced by aldosterone. However, more studies on the role of the NLRP3 inflammasome in the pathogenesis of podocytopathy are still required. The present study was undertaken to study the role of the NLRP3 inflammasome in angiotensin II (Ang II)-induced podocyte injury, as well as the potential mechanisms. Methods: In this study, we used an Ang II infusion model in NLRP3–/– mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 32 publications
3
50
0
1
Order By: Relevance
“…Additionally, the NLRP3 gene is known to be associated with many non-infectious diseases of the nervous system, such as spinal cord injury and X-linked adrenoleukodystrophy (25,26). NLRP3 is also involved in the innate immune response of the body (27). These observations suggest that NLRP3 and inflammatory factors are involved in the occurrence and development of epilepsy.…”
Section: Figure 4 |mentioning
confidence: 99%
“…Additionally, the NLRP3 gene is known to be associated with many non-infectious diseases of the nervous system, such as spinal cord injury and X-linked adrenoleukodystrophy (25,26). NLRP3 is also involved in the innate immune response of the body (27). These observations suggest that NLRP3 and inflammatory factors are involved in the occurrence and development of epilepsy.…”
Section: Figure 4 |mentioning
confidence: 99%
“…ASC deficiency and IL-1R antagonism have blood pressure-lowering and renal anti-inflammatory effects [58,61]. Activation of the NLRP3 inflammasome regulates Ang II-induced podocyte injury by inducing mitochondrial dysfunction, and systemic deletion of NLRP3 can significantly attenuate renal injury resulting from mitochondrial dysfunction [62]. The application of aldosterone can activate NLRP3 in podocytes through oxidative stressrelated mechanisms.…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Recent studies have shown that Ang II can activate and/or trigger various cellular events (e.g. oxidative stress and reactive oxygen species overproduction, endoplasmic reticulum stress, autophagy and mitochondrial dysfunction), thus resulting in cytoskeletal rearrangement and podocyte apoptosis [4][5][6][7][8][9]. Notably, NADPH oxidase (Nox) plays a critical role in driving reactive oxygen species (ROS) production.…”
Section: Introductionmentioning
confidence: 99%